POSITIVE POLITENESS STRATEGY IN “GREATEST SHOWMAN” (19TH CENTURY SOCIETY) AND “CHAPPIE” (21ST CENTURY SOCIETY) MOVIE SCRIPT - Vera Kavita Hartoyo; Agus Salim Mansyur; Toneng Listiani (Universitas Islam Negeri Sunan Gunung Djati, 2019)
The research is a pragmatic study on positive politeness strategies employed by the main characters in “ Greatest Showman” and “Chappie” films in the context of differences certain the century society. the researcher use Brown and Levinson’s theory of positive politeness theory. Politeness is the way of self strategies in communication to others, in order to received their meanings well. The objectives of this research are to find out the types of positive politeness strategies by main character in the setting 19th Century society (Greatest Showman film) and 21st Century setting society (Chappie film) and to find out factors affecting main character to choice that strategies. The researcher used a qualitative method since the data engaged are displayed in the form of strings of words. The result shows that Phineas in “Greatest Showman” that can be conclude in 19th century society, generally showed social class, kept family relation well, and respected for abnormal people. Diffrent with Deon in “Chappie” film that can be conclude in 21st century society, people concern with technology development, a lot of gangster who do the crime, and people communicate only in certain interests.Keywords: Pragmatics, Politeness Strategy, Movie Script